Sifat Fisik, Mekanik dan Barrier Edible Film Berbasis Pati Umbi Kimpul (Xanthosoma sagittifolium) Yang Diinkorporasi dengan Kalium Sorbat - Warkoyo Warkoyo; Budi Rahardjo; Djagal Wiseso Marseno; Joko Nugroho Wahyu Karyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
Xanthosoma sagittifolium starch has the potential to be developed as a base for edible film, because it was hydrocolloid compound, as well as renewable natural resources, widely available and easy to obtain its. High amylose content of X. sagittifolium starch (35.34%), twice than cassava starch, so that it possible to produce strong and flexible edible film. The presence of the active ingredient in edible film with different it kinds and amounts would produce different properties too. The purpose of this study was to evaluate the physical, mechanical and barrier properties of active edible film due to variation of concentration of starch and potassium sorbate. Edible films have produced characteristics for tensile strength from 0.399 to 1.390 MPa, elongation from 14.943 to 31.647%, thickness from 0.065 to 0.081 mm, water vapor transmission rate from 10.095 to 15.247 g.mm/m2.day, solubility from 27.126 to 59.846% and transparency from 0,719 to 1,063. To increase starch made elevation of edible film tensile strength, thickness, WVTR, and the smoothness, as well as decrease its water solubility, while increasing potassium sorbate would increase elongation and WVTR, as well as decrease the tensile strength. ABSTRAKPati umbi kimpul (Xanthosoma sagittifolium) mempunyai potensi untuk dikembangkan sebagai bahan dasar edible film, karena pati merupakan senyawa hidrokoloid, sebagai sumber daya alam yang dapat diperbaharui, tersedia secara luas dan mudah didapat. Kandungan amilosa pati umbi kimpul cukup tinggi (35,34%), dua kali lebih besar dibandingkan amilosa pati ubi kayu, memungkinkan untuk menghasilkan edible film yang kuat dan fleksibel. Keberadaan kalium sorbat dalam edible film dengan jumlah yang berbeda akan menghasilkan sifat yang berbeda pula. Tujuan penelitian ini adalah untuk mengetahui sifat fisik, mekanik dan barrier edible film aktif akibat variasi konsentrasi pati umbi kimpul dan kalium sorbat. Edible film yang dihasilkan mempunyai karakter kuat tarik 0,399-1,390 MPa, persen pemanjangan 14,943-31,647%, ketebalan 0,065-0,081 mm, WVTR 10,095-15,247 g.mm/m2.hari, kelarutan 27,126-59,846% dan transparansi 0,719-1,063. Penambahan pati menyebabkan kuat tarik, ketebalan, laju transmisi uap air, dan kehalusan permukaan edible film meningkat, tetapi kelarutannya dalam air menurun, sedangkan penambahan kalium sorbat dalam edible film menyebabkan persen pemanjangan dan laju transmisi uap air meningkat, tetapi kuat tariknya menurun.